ANALISIS PENGARUH MARKET TIMING ABILITY, STOCK SELECTION SKILL, EXPENSE RATIO DAN TINGKAT RISIKO TERHADAP KINERJA REKSA DANA SAHAM (Studi Pada Reksa Dana Saham Jenis KIK Periode 2009-2013) - Mungkas Putri, Cicilia Heny; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2014)
Mutual funds are other investment opportunities with measurable risk and return is high enough with enough capital affordable to the community. Mutual funds have an Investment Manager with the ability and knowledge of the market it is or will happen. Therefore, mutual funds selected by investors because it is cheap, easy and "managed by the experts".This research analyst do market timing ability, stock selection skill, expense ratio and the risk level can influence the performance of equity mutual funds in Indonesia. The data used in this research are monthly data on Net Asset Value (NAV), SBI, IHSG, yearly data of expense ratio and prospectus of 12 equity mutual fund that were taken by using purposive sampling method during this research report from January 2009 to December 2013. This research used a descriptive analysis, F test and t test to examine research’s hypothesis, also used assumption classic test there are normality test, autocorrelation test, heteroscedasticity test and multicolinearity test using SPSS Statistics 17.0 program.Based on the results of hypothesis testing showed that stock selection skill and market timing ability positively significant influence toward equity mutual fund’s performance, expense ratio negatively significant influence toward equity mutual fund’s performance while the risk level positively not significant influence toward equity mutual fund’s performance.